2006
DOI: 10.1089/thy.2006.16.25
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Deiodination in Birds

Abstract: Because the avian thyroid gland secretes almost exclusively thyroxine (T4), the availability of receptor-active 3,3',5-triiodothyronine (T3) has to be regulated in the extrathyroidal tissues, essentially by deiodination. Like mammals and most other vertebrates, birds possess three types of iodothyronine deiodinases (D1, D2, and D3) that closely resemble their mammalian counterparts, as shown by biochemical characterization studies in several avian species and by cDNA cloning of the three enzymes in chicken. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 80 publications
2
27
0
Order By: Relevance
“…As a consequence of the decreased 5'D activity, less T 4 is converted to T 3 , which leads to an increase in the circulating concentration of T 4 (Darras et al, 2006). We also found increased T 4 concentrations in the restricted groups as compared to controls.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…As a consequence of the decreased 5'D activity, less T 4 is converted to T 3 , which leads to an increase in the circulating concentration of T 4 (Darras et al, 2006). We also found increased T 4 concentrations in the restricted groups as compared to controls.…”
Section: Discussionsupporting
confidence: 47%
“…Decuypere et al (2005) and Kühn et al (2005) found that TRH is not thyrotropic (does not increase plasma concentration of T 4 ), but somatotropic [increases growth hormone (GH) plasma concentration] in adult chickens. TRH administration is followed by increased circulating concentration of GH, and GH decreases 5D (Darras et al, 2006), while it probably increases 5'D (Geris et al, 1998;Kühn et al, 2005). In this way, serum T 3 concentrations are not only decreased due to the reduced T 4 -to-T 3 conversion but also by the increased T 3 -to-T 2 degradation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This differential response to PTU between mammalian D1 and the amphibian and teleostean orthologs probably reflects a difference in the function of the enzyme in these species. In mammals and chicken, D1 is usually highly expressed in the liver, which plays an important role in regulating plasma T 3 levels (reviewed in Darras et al (2006) and Gereben et al (2008)). By contrast, D1 function in teleostean and amphibian T 3 plasma regulation is less clear (Finnson et al 1999.…”
Section: Biochemical Propertiesmentioning
confidence: 99%
“…Therefore, these are called hormoneexporting organs (116,117,119) . D2 is also expressed in the liver in birds but not in mammals (102) . Peripheral tissues can adjust the ratio of active and inactive thyroid hormones, according to their actual energy needs and energy supply through their deiodinase activity.…”
Section: Thyroid Hormonesmentioning
confidence: 97%